1992
DOI: 10.1002/bjs.1800790405
|View full text |Cite
|
Sign up to set email alerts
|

Role of selective decontamination in surgery

Abstract: Aspects of selective decontamination as an antibiotic prophylaxis in general surgery are discussed with respect to the respiratory tract and wound infection. The high rate of nosocomial infection encountered in surgical patients, who experience up to 71 per cent of all such infection, is considered. The infection rate increases to 70-80 per cent after 1 week in the surgical intensive care unit, while the infection-related mortality rate rises to up to 60 per cent. The endogenous origin of nosocomial infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…These nosocomial infections usually occur after 48 h of admission and are mostly caused by aerobe Gram-negative microorganisms. 4,5 These Gram negatives generally originate from the patient's digestive tract. Colonization of the digestive tract with potentially pathogenic microorganisms (PPMs) can harm the patient in two different ways.…”
Section: Introductionmentioning
confidence: 99%
“…These nosocomial infections usually occur after 48 h of admission and are mostly caused by aerobe Gram-negative microorganisms. 4,5 These Gram negatives generally originate from the patient's digestive tract. Colonization of the digestive tract with potentially pathogenic microorganisms (PPMs) can harm the patient in two different ways.…”
Section: Introductionmentioning
confidence: 99%
“…By eliminating or severely reducing the aerobic flora of the bowel lumen the synergy between aerobic and anaerobic bacteria is disturbed and abscess formation reduced. We have not assessed the incidence of postoperative chest infection in this study, but there is evidence that preoperative selective decontamination may also reduce the incidence of this complication [16].…”
Section: Discussionmentioning
confidence: 99%
“…A combination of antibiotic and antifungal medication is given as a paste to the mouth and orally to eliminate the fungal and aerobic bacterial contamination of the GIT. This regimen has been shown to reduce the incidence of nosocomial infections but not to reduce the mortality in these seriously ill patients [16,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option would be to eliminate all potentially pathogenic gram-negative bacteria and fungi in the digestive tract by selective decontamination (SD) [35,36]. Luiten et al showed a reduced mortality in patients with necrotizing pancreatitis when infection of the pancreatic tissue was prevented by SD [37].…”
Section: Microbiology and Antimicrobial Therapymentioning
confidence: 99%